Biomarkers of minimal residual disease in rituximab‐treated patients with mixed cryoglobulinemia. (17th May 2020) - Basile, Umberto; Gulli, Francesca; Napodano, Cecilia; Pocino, Krizia; Basile, Valerio; Marrapodi, Ramona; Colantuono, Stefania; Todi, Laura; Marino, Mariapaola; Rapaccini, Gian Ludovico; Visentini, Marcella
Abstract: Hepatitis C virus (HCV) represents the major risk factor for mixed cryoglobulinemia (MC), a small‐vessel vasculitis that may evolve into an overt B‐cell non‐Hodgkin's lymphoma. Here, we aimed to identify a biomarker signature for the early diagnosis of minimal residual disease (MRD). We assessed free light chains (FLCs), IgM k, and IgM λ heavy/light chain (HLC) pairs, and vascular endothelial growth factor (VEGF) in sera from 34 patients with MC vasculitis (32 HCV‐ and 2 HBV‐related), treated with low‐dose rituximab (RTX). FLCs and IgM HLCs were measured by turbidimetric assay; VEGF by an enzyme‐linked immunosorbent assay. After RTX, the positive (complete + partial) clinical and laboratory responses were of 85.29% and 50%, respectively; in contrast, the mean levels of FLCs, IgM HLCs, and VEGF were substantially unaffected in most patients and still above the normal range. In those achieving a reduction of FLCs and IgM k and λ chains values within the range of normality, we found that post‐treatment free λ chains and IgM k values correlated with clinical and laboratory response. Our results suggest that high levels of FLCs, IgM HLCs, and VEGF could represent the signature of "dormant" B cell clones' activity that could be very useful to identify MRD indicative of possible relapse or worsening outcome. Abstract : Suggested biomarkers of minimal residual disease after rituximab‐treatment in patients with HCV‐related mixed cryoglobulinemia.